Obraz židů u pražských novinářů: Znalosti o židovském náboženství, kultuře, dějinách - Novotná, Hedvika (Lidé města, 2000)
The research conducted within the framework of the Institute of Basic Education of Charles University focused on the knowledge and general consciousness of Czech journalists about Jewish history and culture. From an assessment of answers from 80 respondents it was established that the knowledge of notions associated with Judaism and the life of Jews is far from satisfactory among the group under observation. Most of those surveyed were unable to even approximately explain the notions such as "JHVH", "torah" or "kibbutz". When it comes to the assessment of various periods of Czech history with regard to tolerance of Jews the results were not much better. Basically, the bigger the distance of the period under consideration from now, the more negative assessment was given by those polled, except World War Two. lt is noteworthy that when the journalists were to spontaneously name some distinguished Jewish personalities, they only agreed on Franz Kafka and Albert Einstein. Most respondents described as typical symbols of Jewry only some of the signs of the Jewish religion or some attributes of "Jewish appearance," tainted with prejudice. Most of them agreed that the Holocaust question should not be highlighted more often than it is now. Generally, the knowledge of those shaping public opinion through the media does not exceed the knowledge of their readers or listeners.